2017
DOI: 10.15318/fungus.2017.36
|View full text |Cite
|
Sign up to set email alerts
|

Macrofungal Diversity of Yalova Province

Abstract: Fungal samples were collected from different localities in the boundaries of Yalova province between 2010 and 2012. As a result of field and laboratory studies, 91 species within the 41 families and 14 orders were identified. 17 of them belong to the division Ascomycota and 74 to Basidiomycota. The species list is given with the informations on localities, habitats, collecting dates and collection numbers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…According to the table, the number of taxa that are common in each study was found as twelve, and these species are A. pantherina, A. mellea, C. cibarius, F. fomentarius, H. fasciculare, L. betulinus, L. nuda, L. pyriforme, M. procera, P. ostreatus, S. commune, S. aeruginosa, T. versicolor, and X. hypoxylon. The similarity rates of the studies are 17.84% for Kocaeli (Akata et al 2018), 10.98% for Bursa region (Gücin et al 1995), 11.37% for İznik Region (Allı et al 2016), and 8.23% for Yalova region (Allı et al 2017).…”
Section: Species With High Distribution Inmentioning
confidence: 85%
See 1 more Smart Citation
“…According to the table, the number of taxa that are common in each study was found as twelve, and these species are A. pantherina, A. mellea, C. cibarius, F. fomentarius, H. fasciculare, L. betulinus, L. nuda, L. pyriforme, M. procera, P. ostreatus, S. commune, S. aeruginosa, T. versicolor, and X. hypoxylon. The similarity rates of the studies are 17.84% for Kocaeli (Akata et al 2018), 10.98% for Bursa region (Gücin et al 1995), 11.37% for İznik Region (Allı et al 2016), and 8.23% for Yalova region (Allı et al 2017).…”
Section: Species With High Distribution Inmentioning
confidence: 85%
“…Among the edible and used as food taxa, 16 are collected and consumed in the region by Vill.rs. Members of the genus Morchella are known as "Kuzu göbeği", M. procera as "Dedebörü, şemsiye mantarı", P. ostreatus as "Kavak mantarı, geyik mantarı", L. deliciosus and L. salmonicolor as "Kanlıca", A. caesarea as "Gelincik mantarı, yumurta mantarı, sarı paça", A. campestris as "Çayır mantarı, içi kızıl", C. comatus as "Söbelen", B. edulis as "Ayı Mantarı, sünger mantarı", There exist fungal data on some nearby regions of our study area with former studies in İznik (Allı et al 2016), Yalova (Allı et al 2017), Bursa (Gücin et al 1995) and in Kocaeli (Akata et al 2018). The comparative distribution of the species numbers identified in these studies is given in Table 2.…”
Section: Species With High Distribution Inmentioning
confidence: 99%
“…Both taxa have previously been presented from Turkey only once. Alpova diplophloeus is a member of the order Boletales and sixteen hypogeous members of this order belonging to four families and five genera (Octaviania Vittad., Alpova C.W.Dodge, Melanogaster Corda, Rhizopogon Fr., Sclerogaster R.Hesse) have so far been reported from Turkey (Demirel, 1996;Kaşık et al, 2002;Sesli and Castellano, 2009;Uzun et al, 2014;Sesli and Moreau, 2015;Türkoğlu et al, 2015;Elliot et al, 2016;Allı et al, 2017;Öztürk et al, 2017;Türkekul, 2017;Kaygusuz et al, 2018;Uzun et al, 2019) .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have been carried out on Turkish macromycota and some of them are still in progress Akata and Uzun, 2017;Akata et al, 2015a,b, Alkan et al, 2016Allı et al, 2017;Altuntaş et al, 2017;Demirel et al, 2016;Doğan and Kurt, 2016;Öztürk et al, 2017;Sesli and Denchev, 2008;Sesli et al, 2016). According to the present literature, some investigations on macrofungal taxonomy around the research area were carried out by , , Karamanoğlu and Öder (1973), Öztürk et al (1990), Solak andGücin, 1992;Stojchev et al (1998).…”
Section: Figure 1 Map Of the Research Areamentioning
confidence: 99%